FAKTOR-FAKTOR YANG MEMENGARUHI PERILAKU NEGATIF PADA SISWA REMAJA - Karimah, Ummah; Daffa Akmal, Mochammad; Ayuhan, Ayuhan; Adawiyah, Robi’atul; Fauzi Lubis, Adlan (Asosiasi Dosen PTKIS Indonesia, 2023)
Negative behavior is much influenced by internal and external factors. Where a very difficultsituation in adolescence, one of which is the attitude of self-defense when teenagers are influenced by theirfriends. Due to being in an unstable attitude. Parents, teachers, friends and society are part of the factorsthat influence adolescents' negative behavior. This research uses a qualitative approach and a descriptive typeusing a case study. Data collection techniques using interviews, observation, and additional documents. Dataanalysis was carried out by collecting data, presenting data, and drawing conclusions. As for checking thevalidity of the data in this study using credibility through source triangulation, technical triangulation, andtime triangulation. The results of this study indicate that the factors that influence the occurrence of negativebehavior are the influence of friends, social media, the environment, and parenting styles.